Spectroscopic probe of atomically thin domains of CVD-grown MoSe2 - Singh, Vineeta; Late, Dattatray J.; Rath, Shyama (AIP Conference Proceedings, 2020)
Since the discovery of graphene, two-dimensional Layered Transition Metal Dichalcogenides (TMDCs) such as MoS2, MoSe2, and WS2 having a tunable bandgap, have emerged as one of the most stable classes of materials making them attractive for various applications. We have investigated the growth mechanism and shape evolution of various domains of CVD-grown MoSe2 on insulating substrates by spectroscopic techniques. The different morphologies were analyzed using Raman and photoluminescence spectroscopies. The transformation from the precursor MoO3 to MoSe2 is found to depend on a number of growth parameters and experimental conditions.